Pengaruh Worklife Balance Dan Beban Kerja terhadap Turnover intention Pada Karyawan Mulia Oil Mill (Sism) - Rai Kovin Basilin olta; Aisyah astaf; Thea Geneveva Josephine Jesajas (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2025)
This study aims to analyze the effect of Work-Life Balance and Workload on Turnover Intention among employees of Mulia Oil Mill (SISM). The research employs a quantitative descriptive approach with a total of 111 respondents. Data were collected through questionnaires using a Likert scale, while data analysis was conducted using multiple linear regression. The findings indicate that Work-Life Balance has a significant effect on Turnover Intention, whereas Workload does not have a significant effect. Simultaneously, Work-Life Balance and Workload influence Turnover Intention with a coefficient of determination (R²) of 0.137, meaning that both variables can only explain 13.7% of the variation in Turnover Intention, while the remaining 86.3% is influenced by other factors beyond this study, such as salary satisfaction, leadership style, and work climate. These findings highlight the need to evaluate Work-Life Balance policies so that they not only provide comfort but also strengthen employees’ emotional attachment. In addition, the company needs to implement more holistic workload management, improve communication, and conduct further research to explore other factors that may affect Turnover Intention.